Thermal conductivity of molecular crystals of monoatomic alcohols: from methanol to butanol - Korolyuk, O.A. (Физика низких температур, 2011)
Experimental data on the thermal conductivity κ(T) of some simple alcohols have been compared, analyzed and generalized. The objects of investigation were methyl, protonated and deuterated ethyl, 1-propyl and 1-butyl alcohols in the thermodynamically equilibrium phase with a complete orientational order. The temperature interval was from 2 K to the melting point under the equilibrium vapor pressure. It is found that in the region above the temperature of the maximum thermal conductivity κ(T) deviates from the 1/Т law. This is because the total thermal conductivity has an extra contribution κII(T) of short-lived phonons in addition to κI(T) contributed by propagating phonons: κ(T) = κI(T) + κII(T). The contribution κI(T) is well described by the Debye–Peierls model allowing for the phonon–phonon processes and scattering of phonons by dislocations. At Т > 40 K the contribution κI(T) obeys the law A/Т and κII(T) is practically temperature-independent. It is shown that the Debye temperature ΘD of alcohol is dependent on the molecular mass as ΘD = 678М⁻⁰.⁴² K and the coefficient А characterizing the intensity of the phonon–phonon scattering increases with the molecular mass of the simple monoatomic alcohol by the law А = 0.85М⁰.⁸ W/m, which suggests a decreasing intensity of the phonon–phonon process.